The Long Non-Coding RNA Nostrill Regulates Transcription of Irf7 Through Interaction With NF-κB p65 to Enhance Intestinal Epithelial Defense Against Cryptosporidium parvum - Mathy, Nicholas W.; Deng, Silu; Gong, Ai-Yu; Li, Min; Wang, Yang; Burleigh, Olivia; Kochvar, Andrew; Whiteford, Erin R.; Shibata, Annemarie; Chen, Xian-Ming (Frontiers in Immunology, 2022)
The cells of the intestinal epithelium establish the frontline for host defense against pathogens in the gastrointestinal tract and play a vital role in the initiation of the immune response. Increasing evidence supports the role of long non-coding RNAs (lncRNAs) as critical regulators of diverse cellular processes, however, their role in antimicrobial host defense is incompletely understood. In this study, we provide evidence that the lncRNA Nostrill is upregulated in the intestinal epithelium following infection by Cryptosporidium parvum, a globally prevalent protozoan parasite that causes significant diarrheal disease and an important opportunistic pathogen in the immunocompromised and AIDS patients. Induction of Nostrill in infected intestinal epithelial cells was triggered by NF-κB signaling and was observed to enhance epithelial defense by decreasing parasitic infection burden. Nostrill participates in the transcriptional regulation of C. parvum¬-induced Irf7 expression through interactions with NF-κB p65, and induction of Nostrill promotes epigenetic histone modifications and occupancy of RNA polymerase II at the Irf7 promoter. Our data suggest that the induction of Nostrill promotes antiparasitic defense against C. parvum and enhances intestinal epithelial antimicrobial defense through contributions to transcriptional regulation of immune-related genes, such as Irf7.